Sports Therapist Training For Dikoni Coaches In Mataram City - Soemardiawan, Soemardiawan; Yundarwati, Susi; Anggraini, fitri; Marzuki, Ismail (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
In the world of sports, an athlete's success is not only determined by intensive training but also by proper physical recovery management. One aspect that is often overlooked yet very important is recovery through sports massage techniques. The main problem identified is the lack of specialized teams or skilled personnel serving as sports masseurs or sports therapy experts in most sports branches under KONI Kota Mataram. The goal of this training is to ensure that each sports branch under KONI Mataram has competent supporting personnel in the field of sports massage, namely sports therapists. The method used in this service is the expository method, which is a learning method delivered by first providing lectures that explain supporting materials such as injury massage, discussions, definitions, principles and concepts of the subject matter, as well as providing examples of practice exercises, demonstrations, qustions, and assignments, as well as knowledge training both in theory and practice. The research results can be concluded to provide an understanding of the basic theory and practice of sports therapy in sports massage for the measurement team under KONI Mataram, preparing the measurement team, and improving athletes' recovery quality through skilled personnel in the field of sports massage.